2016
DOI: 10.1080/02673037.2016.1150431
|View full text |Cite
|
Sign up to set email alerts
|

‘Extra oomph:’ addressing housing disparities through Medical Legal Partnership interventions

Abstract: Low-income households face common and chronic housing problems that have known health risks and legal remedies. The Medical Legal Partnership (MLP) program presents a unique opportunity to address housing problems and improve patient health through legal assistance offered in clinical settings. Drawn from in-depth interviews with 72 patients, this study investigated the outcomes of MLP interventions and compares results to similarly disadvantaged participants with no access to MLP services. Results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Domestic violence/family law and housing were the main socio-legal concerns addressed by the MLP. This is consistent with other MLP studies, including those conducted in ambulatory care clinics [14,15]. Domestic or intimate partner violence (IPV) is common, affecting more than 1 in 3 women and 1 in 4 men [16].…”
Section: Patientssupporting
confidence: 90%
See 1 more Smart Citation
“…Domestic violence/family law and housing were the main socio-legal concerns addressed by the MLP. This is consistent with other MLP studies, including those conducted in ambulatory care clinics [14,15]. Domestic or intimate partner violence (IPV) is common, affecting more than 1 in 3 women and 1 in 4 men [16].…”
Section: Patientssupporting
confidence: 90%
“…The prevalence of civil legal needs among individuals experiencing homelessness and unstable housing situations is very high (more than 90%) based on a survey of a national sample of 48 homeless service sites across 26 states [20]. Studies have shown that low-income individuals with hous-ing issues who receive MLP services were more likely to get adequate, affordable, and stable housing than similar individuals in the same community who did not have access to MLP services [15]. Despite this, few sites that serve this vulnerable population have MLPs [20].…”
Section: Patientsmentioning
confidence: 99%
“…Set within the larger context of neighborhood disadvantage, factors such as racial residential segregation, concentrated poverty, limited social cohesion and deficient institutions produce a backdrop of structural challenges with direct implications for the availability of a decent housing stock. Unsafe neighborhood conditions also amplify the salience of the home environment as people stay home more often to avoid violence and danger (Hernández, 2016a,b). As an additional layer of disadvantage, housing marked by deficiencies in quality and lacking modern efficiencies affect the conditions of the home environment and the costs associated with its operation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The key dimensions of energy insecurity emerged using an adapted grounded theory approach in a qualitative study originally conducted to explore broad housing problems among low-income families (Hernández, 2016a; 2016b). The present analysis focused on energy as a unique housing problem and addressed the following research questions: (a) What are the primary dimensions of energy insecurity?…”
Section: Methodsmentioning
confidence: 99%
“…Feedback gathered from project staff in a variety of international settings suggests that HJPs provide a more rounded service for patients, addressing interconnected health and welfare issues in a comprehensive way [ 5 , 16 , 74 ]. Partnership working between health and legal services helped to resolve issues affecting health and wellbeing and was felt to make a positive contribution to patient care [ 45 , 75 ]. Patients reported valuing the continuity of support, familiarity and personalized service [ 16 ].…”
Section: Resultsmentioning
confidence: 99%